Applied Mechanics 2005
DOI: 10.1115/imece2005-79709
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Considerations for Ballistic Limit Equations for Aerospace Structural Systems

Abstract: The overall risk for any spacecraft system is typically determined using a Probabilistic Risk Assessment (PRA). A PRA determines the overall risk associated with a particular mission by factoring in all known risks to the spacecraft during its mission. The threat to mission and human life posed by the mircro-meteoroid and orbital debris (MMOD) environment is one of the risks. NASA uses the BUMPER II program to provide point estimate predictions of MMOD risk for the Space Shuttle and the ISS. However, BUMPER II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…This is due to the typical steep variation of the flux (in the mass range of interest for most of failure modes and for most of the environment models) as a function of the particle size. The sensitivity study [8] mentioned above reported an increase in the failures level as high as 120 per cent for a decrease in the critical size predicted by the BLEs of a mere 20 per cent. On the other side, an increase by 20 per cent of the critical size predicted by the BLE was reported to decrease the predicted risk level by more than 50 per cent.…”
Section: Damage Equations and Hypervelocity Impact Testsmentioning
confidence: 86%
See 1 more Smart Citation
“…This is due to the typical steep variation of the flux (in the mass range of interest for most of failure modes and for most of the environment models) as a function of the particle size. The sensitivity study [8] mentioned above reported an increase in the failures level as high as 120 per cent for a decrease in the critical size predicted by the BLEs of a mere 20 per cent. On the other side, an increase by 20 per cent of the critical size predicted by the BLE was reported to decrease the predicted risk level by more than 50 per cent.…”
Section: Damage Equations and Hypervelocity Impact Testsmentioning
confidence: 86%
“…These uncertainties in the environment models affect the results of the probabilistic risk assessment. According to a sensitivity study of the dependence of MMOD risk prediction for the shuttle on several assumptions and parameters [8], the variations in the number of failures can be assumed to scale linearly with variations in the number of particles (i.e. fluxes).…”
Section: Meteoroids and Debris Environment Modelsmentioning
confidence: 99%
“…In order to assess the "goodness of fit" for the new BLEs and compare it that of the original NNO BLE, we can use specificity and sensitivity ratios, which are defined as follows (see [26] for additional information regarding these quantities):…”
Section: Discussionmentioning
confidence: 99%
“…This issue, as well as techniques that can be used to statistically derive BLEs for dual-wall structures, is discussed in more detail in Ref. [11]. In the discussions that follow, original, non-reduced values of critical diameters as calculated by the current NASA/JSC BLE are used.…”
Section: The Nasa/msfc Test Databasementioning
confidence: 99%